الإجارة المنتهية بالتمليك عند المالكية - شارف, عبد الجبار; بحاد, جيلاني (University of Eloued-جامعة الوادي, 2017)
ملخص البحث يهدف هذا البحث إلى دراسة: "الإجارة المنتهية بالتمليك عند المالكية"، وهو من صيغ التمويل الإسلامية وله أهمية كبيرة في تنمية عدد من القطاعات الاقتصادية، وقد تناول البحث هذا العقد عبر: مدخل ذكرت فيه نشأت الإجارة المنتهية بالتمليك وأهم المناطق التي تواجد فيها، ثم مبحث أول: للتعريف به ودراسة مشروعيته وأركانه وشروطه والتفريق بينه وبين غيره من العقود، ثم مبحث ثاني: لدراسة اشتراطات هذا العقد وتكييف صوره التطبيقية المتداولة، ومبحث ثالث: لدراسة أهم المسائل المتعلقة به من ضمان وصيانة وأحكام الأجرة، مع ذكر أهم الحالات التي يكون بها انتهاء وفسخ هذا العقد، وذلك من خلال آراء المذهب المالكي. وتوصل في الأخير إلى خاتمة تضمنت أهم النتائج والتوصيات. Search Summary The aim of this research is to study: "The expired rent by titling in Al-Maliki doctrine", which is one of the islamic funding formulas that has a great importance in the development of such a number of economic sectors. The research has addressed this contract through the expired rent by titling mentioned in an introduction and the most important areas in which it is located. First, to define it and to study its lawfulness, its elements and conditions, then differentiate it from other contracts. Second, To study the requirements of this contract and to adapt its current applied images. Third, To study the most important issues relating to it as the guarantee, maintenance and remuneration of the fare, with this most important cases of termination and avoidance of the contract, through Al-Maliki doctrine views. Finally, the search reached a conclusion that included the most important results and recommendations.
مذكرة ليسانس
Keywords: الاجازة /التمليك /المالكية; Vacances/propriété/propriété